A Connecting Mobile Marketing Events and Business Performance During Covid-19 Business Crisis in Africa - Alberto Ndekwa (International Journal of Marketing & Human Resource Research, 2021)
This chapter focused on analyzing the influence of mobile marketing on Business Performance during COVID 19 business crisis in Africa. Quantitative data was collected using questionnaire to a total sample of 343 respondents who are the business owners in Tanzania. Simple sampling technique was used to pick where questionnaire were used to collect data for statistical analysis. Secondary data was collected through documentary review to support and interpret findings from primary data collected using surveyed questionnaire. Data analysis using structural equation modeling revealed that mobile marketing is significant influencing business performance during COVID 19 business cries. The significance influence of mobile marketing is explained by the fact that mobile marketing offers online payment, online advertisement and online promotion which in turn increases market share, increases sales and revenue of the business. It is concluded that for business to perform during COVID 19, owners of the business should use mobile marketing for performing online payment, online advertisement and online promotion especially during the time of observing social distancing and business lockdown.  Addition, it is concluded that connecting mobile marketing and business performance helps to alleviate COVID 19 business crisis in Africa. This chapter recommends that the business sector should design and implement the mobile marketing to offset business crisis for business performance during COVID 19 business crisis. On the other hand, this chapter recommends that training to be conducted to owners of the business in order to educate them and create the awareness of the perceived benefit of mobile marketing for business performance during COVID 19 crisis.